Deficiency of Viral Ribonucleic Acid-Dependent Deoxyribonucleic Acid Polymerase in Noninfectious Virus-Like Particles Released from Murine Sarcoma Virus-Transformed Hamster Cells - Peebles, P. T. (1972)
Virions from hamster cells transformed by a new strain of murine sarcoma virus (MSV) appear to represent a form of MSV deficient in one or more of the viral components necessary for infectivity. Both the noninfectious virions and the sarcoma virus-transformed cells, which have no detectable replicating leukemia helper virus of either murine or hamster origin, are deficient in viral-type ribonucleic acid (RNA)-dependent deoxyribonucleic acid (DNA) polymerase activity (i.e., reverse transcriptase activity stimulated by the synthetic RNA-DNA template polyribo-adenylic-oligodeoxythymidylic acid). In comparison, both murine leukemia virus (MuLV) and MuLV-infected cells have abundant viral-type reverse transcriptase activity. It appears, therefore, that the leukemia virus genome may be required for the production of infectious sarcoma virus by contributing information needed for the full expression of functional viral-type reverse transcriptase.